Ullmann's Encyclopedia of Industrial Chemistry 2006
DOI: 10.1002/14356007.a08_139.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cyanamides

Abstract: The article contains sections titled: 1. Calcium Cyanamide 1.1. Physical Properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Cyanamide 7 (p K a =10.3 in H 2 O)[48] is known to dimerise in aqueous solution. [49] The rise in pH would allow access to the conjugate base 23 , which could undergo nucleophilic attack onto 1 to give cyanoguanidine 24 (Scheme 5).…”
Section: Resultsmentioning
confidence: 99%
“…Cyanamide 7 (p K a =10.3 in H 2 O)[48] is known to dimerise in aqueous solution. [49] The rise in pH would allow access to the conjugate base 23 , which could undergo nucleophilic attack onto 1 to give cyanoguanidine 24 (Scheme 5).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed it was found that 0.06% MMS treatment for 2 h resulted in approximately 90% cell death, while 0.015% MMS treatment for 2 h has very little if any toxicity (Figure 1E ). On the other hand, cyanamide has been used as a herbicide and fungicide due to its mild toxicity ( Güthner and Mertschenk, 2000 ). Little is known about the relative sensitivity of yeast to cyanamide, although we previously demonstrated that budding yeast cells lacking the cyanamide hydratase activity displayed an enhanced sensitivity to cyanamide ( Li et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…2014). In Germany, there is official recognition of DCD's properties (Nõmmik 1958; Anon 1996; Güthner & Mertschenk 2006).…”
Section: Fertilizer Valuementioning
confidence: 99%